2019
DOI: 10.1186/s12964-019-0426-3
|View full text |Cite
|
Sign up to set email alerts
|

N822K- or V560G-mutated KIT activation preferentially occurs in lipid rafts of the Golgi apparatus in leukemia cells

Abstract: Background KIT tyrosine kinase is expressed in mast cells, interstitial cells of Cajal, and hematopoietic cells. Permanently active KIT mutations lead these host cells to tumorigenesis, and to such diseases as mast cell leukemia (MCL), gastrointestinal stromal tumor (GIST), and acute myeloid leukemia (AML). Recently, we reported that in MCL, KIT with mutations ( D816V , human; D814Y , mouse) traffics to endolysosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 76 publications
4
21
0
Order By: Relevance
“…Recently, we reported that in MCL, KIT D816V (human) or KIT D814Y (mouse) activates STAT5 and AKT on the ER and endolysosomes, respectively 21,25 , whereas KIT V560G in MCL activates downstream at the Golgi apparatus 24 . Furthermore, KIT mutants including KIT D816V in cells other than MCL, such as GIST and leukemia cells, cause oncogenic signals on the Golgi apparatus 22,24,33 . As previously described 4,18,19 , we confirmed that after biosynthesis in the ER, FLT3-ITD causes STAT5 tyrosine phosphorylation in a manner similar to KIT D816V in MCL.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we reported that in MCL, KIT D816V (human) or KIT D814Y (mouse) activates STAT5 and AKT on the ER and endolysosomes, respectively 21,25 , whereas KIT V560G in MCL activates downstream at the Golgi apparatus 24 . Furthermore, KIT mutants including KIT D816V in cells other than MCL, such as GIST and leukemia cells, cause oncogenic signals on the Golgi apparatus 22,24,33 . As previously described 4,18,19 , we confirmed that after biosynthesis in the ER, FLT3-ITD causes STAT5 tyrosine phosphorylation in a manner similar to KIT D816V in MCL.…”
Section: Discussionmentioning
confidence: 99%
“…Mutant KIT in leukemia localizes to endosome-lysosome compartments through endocytosis, whereas that in GIST stops in the Golgi region during early secretory trafficking. We further showed that blockade of KIT trafficking to the signal platform inhibits oncogenic signals [24][25][26] , suggesting that trafficking suppression is a novel strategy for suppression of tyrosine phosphorylation signals.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations